Interventional cardiology : principles and practice - Dangas, George D.; Ohio Library and Information Network (Hoboken, NJ: John Wiley & Sons, Inc., 2022)
"The modular presentation of this textbook, both as a printed book, as well as e-book CD rom or web-based program reflects the effort of the publisher and the editors to reach out to many generations of physicians in training. The evolution of specialty certification and recertification has indeed made life learning a reality in our era. Therefore, the present textbook must also fulfill the quest to approach the new and tech-savvy learner, those ahead of an initial certification examination, those in advanced clinical practice who need practical instruction for a certain specialized subject, as well as those who have been practicing for a long time and need to refresh their knowledge with or without a recertification examination ahead of them. We hope that readers will find our approaches both useful and practical"--
Keywords: Heart -- Surgery; Coronary heart disease -- Surgery; Cardiovascular Diseases -- therapy; Cardiac Surgical Procedures; Cardiovascular Diseases -- diagnosis; Electronic books